Jaringan Sosial dalam Membangun Usaha Pengolahan Hasil Tani - Soenaryo, Terry Franka; Bakti, Muhammad Iqbal Putra; Gleetus, Ario; Yanto, Hendy Defri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Rowosari Village is an agrarian community with advanced agricultural and agricultural processing sectors. These sectors have been well-developed for a long time and receive support from various parties. One of the significant agricultural processing enterprises is owned by Mr. Rudi. The agricultural products processed include rice and corn. The growth of this enterprise involves many parties providing support in the form of funds and processing machines. Additionally, there is a cooperative and farmer groups established by Mr. Rudi himself, which have significantly assisted his business. The purpose of this research is to dissect the networks built within and outside of production relations and how the owner has managed to expand the agricultural processing business to its current size using Social Network theory by focusing on the concept of Embeddedness. This research uses qualitative methods with an ethnographic approach, as the focus of the study lies on the community, specifically the agricultural processing business situated in a rural society.